Exosomal Immune Checkpoint Molecules as Liquid Biopsy Markers (International Journal of Scientific Research in Science and Technology, 2024)
Immune checkpoint inhibitors have revolutionized the management of cancer; unfortunately, there are few stable and least invasive biomarkers in forecasts and monitoring of therapeutic response. Traditional tissue biopsies do have limitations in the heterogeneity of tumors, invasiveness of the procedure and a limited temporal model. Liquid biopsy is therefore an emerging alternative and increasing evidence is presenting the tumor-derived exosomes as information-rich circulating biomarkers. Exosomes are directly engaged in tumorimmune crosstalk capable of carrying immune checkpoint molecules, programmed death-ligand 1 (PD-L1), programmed death-1 (PD-1), and other co-inhibitory controls, and is involved in immune escape and therapy resistance. Recent publications also show that exosomal immune checkpoint molecules can not only indicate the dynamism of the immune status of the tumor microenvironment, but also offer better stability and sensitivity than soluble or cell-based biomarkers. This review critically analyses the biological and clinical usefulness and technological improvements connected with exosomal immune checkpoint molecules as markers in liquid biopsy. We address their diagnostic, prognostic and predictive value in a variety of types of cancer, and we pay special attention to the immunotherapy response assay. Existing problems, such as analytical standardization, biological heterogeneity, and clinical validation are also dealt with. Lastly, prospective outlooks into incorporating exosomal immune checkpoint profiling in precision immuno-oncology are discussed highlighting its capacity to direct personalized cancer immunotherapy.